Contribuição do profissional bibliotecário na formação do discente de graduação na universidade - Lira, Elda Lopes (2007)
This study had as the objective to know the representation manifested social an the speech of the librarians professionals working in university libraries about your contribution at formation of the university student of graduation. The research held was qualitative types, having as theoretical and methodological fundamentation the knowledge sociology and the social constructive precepts, besides the social and collective representation theories. The analysis technique for the speechs tabulation, collected by interview, was the Collective Subject Speech (CSS). The research environment was the Central Library of the UFSC, to located in University Campus Trindade, in Florianópolis, in Santa Catarina State. The choice the is institution occorre in consideration suitability of research. The trough of speech synthesize on CSS, mode what the knowledge obtained in graduation form the support for work of librarian and for that he develop your work quotidian of form more efficient, are necessary a heap of knowledge of the languages foreigner, above all of the English. The domain of the work what drudgery in the day by day, the knowledge aggregates at the along of the professional life and the knowledge acquired with the continued education form the conjoined of the professionals competences speak by the speech collective, while what attention, honesty, self-confidence and understanding are mention how the principal personal competences. The computing, the data-bases and the internet are the workman’s tool and the technological recourse utilizable by the collective interview. Kept evident still what promote the autonomy of the student by your research is a objective common between the interview librarian.